ECOLOGICAL STUDY AND SUSCEPTIBILITY OF SOME PEAR VARITIES TO ATTACK BY Dysaphis reaumuri and Dysaphis pyri - Nazar M. Al-Mallah; Haitham M. Mohammed; Abdul Jabar K. AL. Obada (Mesopotamia Journal of Agriculture)
The results of studying the effect of some Ecological factors and Ana and vestibella pear varities on Seasonal activity of leafroll aphid Dysaphis reanmuri and Dysaphis pyri. showed a significant effect on mean number of the two aphid species a ccording to the season . apple varity and direction. the highest mean aphid number reached 29.89 Aphid / Leaf on east direction on vestibella variety for the season 2010 – The results also exhibit a significant variation between the general mean number of aphids according to the direction and reached 21.17، 6.13، 5.41 and 12.7  Aphid / leaf for East . West . North and  South direction respectively . The regression equations between the mean number of aphids and biotic and abiotic factors showed a clear effect on mean aphid seasonal activity and the Temperature exhibit ahighest effect on mean aphid number and reached   ٪85 while the effect of moisture and rain and wind  43.7 ،53.1،37.9  %  for  the season  2009  while of season     reached  52.4،7.14،70.1،60.1  %  in the 2010  respectively